Preliminary checklist of Rhopalocera (Lepidoptera) in Libiki Bamboo Resort, Bau, Sarawak, Malaysia - Jelina Hilo,; Vikneswary Subramaniam,; Stanly Merum Mawar,; Nur Ruzana Ruzaimi,; Nur Farhana Nisha Syazwan,; Reincce Rhyl Bruen Scott,; Sara Dalton Saging,; Muhammad Firdaus Zaidi,; Heranya Sivanesan,; Farah Nabillah Abu Hasan Aidil Fitri,; Madinah Adrus, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
A preliminary study was conducted on the diversity of Rhopalocera (lepidopterans) butterfly fauna present in secondary forest of Libiki Bamboo Resort (LBR), Bau, Sarawak, Malaysia, due to the anthropogenic effect of human disturbance. The objectives of this study are to establish with a preliminary checklist of Rhopalocera and their species diversity in the mentioned resort and recorded its conservation status. Furthermore, this study work was performed to narrow the gap of knowledge regarding the diversity of Rhopalocera in Bau area, as no survey had been conducted in LBR previously. Twenty baited traps (passive method) and five ariel nets (active method) were used to collect Rhopalocera. Baited traps were placed along the trail and set up 100 m from each other with pineapple as bait, where aerial nets were used during day time, once in the morning and once in the evening, with a total sampling effort of 240 hours. A total of 183 butterflies from six families (Hesperiidae, Lycaenidae, Nymphalidae, Papilionidae, Pieridae and Riodinidae) belonging to 63 species under 35 genera were successfully collected and recorded. The most abundance individuals collected and identified were from the family Nymphalidae (75.4%, n = 138), whereas family Hesperiidae was the least family collected (0.5%, n = 1). Based on International Union for Conservation of Nature (IUCN) Red List status, one species, Euploea mulciber was found to be a vulnerable species, while most of the species recorded were categorised as data deficient status (84.13%, 53 species). Hence, it is recommended to conduct multiple similar studies to provide more adequate information for a more accurate update on the conservation status of Rhopalocera species in Malaysia.